The interplay of body composition, pain intensity, and psychological status in Egyptian patients with knee osteoarthritis - Naylan Fayez Wahba Khalil; Marwa Mohamed Hassan; Nehad Mohamed Elshatby (Egyptian Rheumatology and Rehabilitation, 2024)
Abstract Background There is a clear relationship between poor mental health, obesity, and osteoarthritis (OA). Individuals who experience symptoms of anxiety and depression are more likely to report higher levels of pain and disability in OA. In addition, higher body mass index (BMI) levels can contribute to additional pain and disability in individuals with OA. We aimed to explore the interplay of Body composition, pain intensity, and psychological status in Egyptian patients with knee OA. Results This cross-sectional study included 60 patients with Knee OA diagnosed clinically according to the American College of Rheumatology (ACR) criteria. Body composition measurement was performed with an InBody analyzer. Pain was assessed by the pain visual analog scale (VAS), disability was measured with Western Ontario and McMaster Universities Osteoarthritis (WOMAC) scores, and depressed mood and/or anxiety was measured by the Hospital Anxiety and Depression Scale (HADS). Body mass index (BMI), total body fat (TBF) %, fat mass (FM), and fat mass index (FMI) were positively correlated with pain and disability in patients with knee OA. TBF% was positively correlated with depression and anxiety. Conclusions This study has shed light on the association between mental disorders, body composition measurements, knee pain, and disability. Interventions to treat osteoarthritis in elderly patients should focus on treating mood changes such as anxiety and depression, psychological support, and controlling body mass with proper diet and exercise programs.